Pengembangan Model Pembelajaran Senam Irama untuk Siswa Sekolah Dasar - Salbani; Zusyah Porja Daryanto; Suriani Sari (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The objectives of this study were to develop a video-based rhythmic gymnastics learning model for elementary school students to enhance learning outcomes, and to determine the model's feasibility based on expert and user evaluations. The study employed a Research and Development (R&D) approach adapted from the Borg and Gall model, comprising the following stages: needs analysis, product design, design validation, small- and large-group field trials, revisions following these trials, and final productization. Participants included elementary school students involved in small-group trials (10 students) and large-group trials (20 students). Data were collected through interviews, observations, questionnaires, and expert validation sheets involving media experts, subject matter experts, and physical education (PJOK) teachers. Validation results indicated feasibility ratings of 88% from media experts, 93% from subject matter experts, and 94% from physical education teachers, all falling into the "highly feasible" category. The small-group trial (10 participants) yielded an average score of 78.65%, while the large-group trial (20 participants) yielded 82.45%; both results fall within the "highly feasible" category. Keywords: ADDIE Model, Elementary School Physical Education, Learning Media, Rhythmic Gymnastics, Video-Based Learning